Construction, characterization, and growth mechanism of high-density jellyfish-like GaN/SiOxNy nanomaterials on p-Si substrate by Au-assisted chemical vapor deposition approach. Issue 26 (14th June 2019) - Li, Pengkun; Li, Kang; Sun, Shujing; Chen, Chenlong; Wang, B. G.
Abstract : High-density GaN/SiO x N y jellyfish-like nanomaterials are synthesized on Au-coated p-type Si substrates by a chemical vapor deposition approach. Abstract : High-density, well-aligned GaN/SiO x N y nanomaterials with jellyfish-like shape are constructed on Au-coated p-type (111) Si substrates by a convenient chemical vapor deposition method. The morphology, structure, constituents and optical properties of the as-prepared nanomaterials are characterized through field-emission scanning electron microscopy, X-ray diffraction, field-emission transmission electron microscopy, energy-dispersive spectroscopy mapping, and photoluminescence spectroscopy. The systematic characterization results reveal that the high-density jellyfish-like nanomaterials are composed of single-crystalline GaN nanoblocks as jellyfish top-caps with size of 200–600 nm and amorphous SiO x N y nanowires as jellyfish bottom-tentacles with length of several micrometers. A growth mechanism of the jellyfish-like nanomaterials is proposed: Au acts as a capture site for the Ga species from vapor to form Ga–Si alloys, and then the Ga-catalyzed vapor–liquid–solid growth initializes the nucleation and further promotes the growth of silicon dioxide nanowires on the substrate surface; finally, the silicon dioxide nanowires with Ga balls are converted to form the high-density aligned GaN/SiO x N y jellyfish-like nanocomposites by nitridation. The GaN/SiO x N y jellyfish-like unique nanostructures grown on a p-type Si substrate will provide a new GaN-based device structure and offer potential applications in photocatalytic and optoelectronic nanodevices.